Answers

The Brainliest Answer!
2016-02-22T22:03:40+05:30
Let yellow circle be x
Let orange circle be y
Let black circle be z

Given⇒

x + 2y + z = 43
3x + y = 57,    x = (57 - y) / 3
3z + y = 48,    z = (48 - y) / 3

Now, Substituting The Value of x And z in the first equation

57 - y   +    2y    + 48 - y     = 43
--------                   ---------
   3                            3

57 - y + 6y + 48 - y  = 43
--------------------------
              3

105 + 4y = 129
4y = 129-105
4y = 24
y = 24/4
y = 6

Substituting The Value Of y in equation 2 
3x + y = 57
3x + 6 = 57
3x = 57 - 6
3x = 51
x = 51/3 = 17

Now, Substituting The Value Of y in equation 3

3z + y = 48
3z + 6 = 48
3z = 48 - 6
3z = 42
z = 42/3 = 14

Therefore,
x = 17
y = 6
z = 14

Fourth Column = x + 2z + y
                         = 17 + 28 + 6
                         = 51

Value of Fourth Column = 51
If u r satisfied Plz Mark The Answer Brainliest


4 5 4
2016-02-22T22:31:49+05:30
Answer Is 51 for sure i will upload my pic of solution when it get to my computer
2 5 2